1995
DOI: 10.1002/bit.260450305
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium on development of anaerobic acidogenic biofilms

Abstract: Anerobic biofilms with dominantly acidogenic bacteria were grown in fixed-bed recycle reactors. The influence of calcium concentration in the culture medium on biofilm mass accumulation, immobilized calcium concentration, and biofilm-specific activity was investigated. The results indicate that the biofilm mass accumulation was increased by the presence of calcium in the growth medium when calcium concentration was not higher than 120 mg/L. Calcium accumulated in the biofilms increased in proportion to the cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 11 publications
6
20
1
3
Order By: Relevance
“…Hence, analysis of the removal efficiency of Ca 2+ under different aeration intensities, as well as the relevant influencing factors, was important for estimating the negative impact of Ca 2+ on the experiment. As shown in Table 2, despite the high concentration of Ca 2+ in the papermaking wastewater, the biofilm treatment method demonstrated great removal performances for both the large and small aeration intensities, similar to the results of Huang and Pinder (1995). During the formation process of the biofilms, aggregated microbes generate EPS that has the capability of adsorbing and combining part of Ca 2+ onto the biofilms, which can help to construct a more stable biofilm structure with a stronger ability of adjusting to the outer environment (Arp et al 2001).…”
Section: +supporting
confidence: 77%
“…Hence, analysis of the removal efficiency of Ca 2+ under different aeration intensities, as well as the relevant influencing factors, was important for estimating the negative impact of Ca 2+ on the experiment. As shown in Table 2, despite the high concentration of Ca 2+ in the papermaking wastewater, the biofilm treatment method demonstrated great removal performances for both the large and small aeration intensities, similar to the results of Huang and Pinder (1995). During the formation process of the biofilms, aggregated microbes generate EPS that has the capability of adsorbing and combining part of Ca 2+ onto the biofilms, which can help to construct a more stable biofilm structure with a stronger ability of adjusting to the outer environment (Arp et al 2001).…”
Section: +supporting
confidence: 77%
“…The authors hypothesized that calcium was important for stabilizing the biofilm matrix (9). Other studies have also suggested a role for calcium in stabilizing biofilms of bacteria (18,22,39).…”
Section: Discussionmentioning
confidence: 99%
“…The lag time started increasing at calcium chloride concentration of 4 g/l. This phenomenon can be attributed due to the microbial aggregates formed by calcium chloride at higher concentrations (Huang and Pinder, 1995). The microbial aggregates reduced the free microorganisms and thus the effective microbes accessing available substrate in the medium.…”
Section: Effect Of Salts On Bacterial Growthmentioning
confidence: 99%